Is it all in your head? Placebo effects in concussion prevention - Smoliga, J. M.; Bleakley, C.; Pearce, A. J. (Sports Medicine, 2025)
Sports-related concussions (SRCs) are a major health issue in athletes of varying ages, ability levels, and sports. Concerns over the short- and long-term consequences of SRCs have incentivized a wealth of products and policies aimed at reducing SRC risk. Research suggesting the effectiveness of such interventions at reducing SRCs has facilitated their adoption by sports organizations and, in some cases, product commercialization. However, the body of SRC mitigation research is almost entirely devoid of placebo or sham groups, which raises important questions about the true clinical effectiveness of these interventions. This Current Opinion explores the plausibility of placebo effects within the scope of SRC prevention, describes why the lack of placebo/sham groups in the current body of literature is problematic, and provides recommendations for including placebo/sham groups in future SRC research.